PENYEDIAAN DATA SPASIAL BANGUNAN DI SEKOLAH VOKASI UGM DALAM SEBUAH BASISDATA 3D - Muryamto, Rochmad; Mutiarasari, Wahyu Marta (Geoid, 2020)
Spatial data supply activities can be carried out with various data inputs and produce various products. One product that stores spatially structured data is spatial database. Spatial database can support storage of height components (3D) of an object, for example a building. The use of 3D spatial database can be very broad and for various fields of application, one of which is the preservation of cultural heritage. This study aims to provide spatial data in the form of a 3D database for building, especially those that have become cultural heritage, within the UGM Vocational School (SV) environment. This activity uses 3D model data from one of the buildings at UGM, the Vocational School library building. Building 3D model is used as input for designing database modeling. The modeling in LOD 3 is then applied using CityGML, including its semantics. The result of the design is then entered into the software to create 3D database. The database analysis stage is performed with several SQL queries to test the research product in the form of the 3D database. Based on the result, 3D spatial data is stored properly using CityGML schema whereas some semantics cannot be accommodated.